The Indonesian Land Border Security System: A Strategic Decision Making for National Security - Sipahutar, Amos Pedro; Ali, Yusuf; Madjid, Adnan; Putro, Resmanto Widodo (Universitas Sriwijaya, 2024)
Securing the border of a nation is identical with upholding the nation’s sovereignty. Therefore, it is very important to ensure the role of securing the land border area through maximum security according to its needs. Several violations often occur in land border areas between two countries, so it is necessary to maintain strict security along the borders of the two countries. But the problem is, the borders between countries are very long, and it is impossible to deploy TNI troops along these borders. Apart from the difficult terrain conditions in the border areas, there are also a large number of TNI soldiers needed to guard the borders, so this is not an effective and efficient thing to do. This research was conducted based on data on violations in the border areas between the Republic of Indonesia and other countries, namely Malaysia, the Democratic Republic of Timor Leste and Papua New Guinea, which are represented in the distribution of cases during the second semester of 2020 and the first semester of 2021. Based on data collection data from respondents/field practitioners who have been directly involved in securing border areas and with the help of the Analytical Hierarchy Process (AHP) method and the Strengths, Weakness, Opportunities and Threats (SWOT) method, a decision with optimal value regarding the security of land border areas can be determined. appropriate to current and future conditions. Analysis using AHP resulted in the best alternative being a Non-Traditional Deployment (53%) with a consistency ratio value of 0.0136 (1.36%). Likewise, analysis using SWOT produces the best alternative, namely Non-Traditional Deployment with an IFAS score of 0.12 and EFAS 0.90. So, the best alternative that should be taken by decision makers in order to realize land border security in order to strengthen Indonesia's defense strategy is to use the Non-Traditional Deployment system.